2010
DOI: 10.1143/jjap.49.07hf16
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Signal Characterization of Phase Change Nanodroplets in Tissue-Mimicking Phantom Gels

Abstract: To apply superheated perfluorocarbon nanodroplets to tumor diagnosis and treatment, acoustic signals formed upon the vaporization of droplets in tissue-mimicking phantoms were measured with 3 MHz ultrasound. A characteristic impulse wave was associated with phase change induction with 100 cycles of ultrasound at a 9 MPa peak negative pressure, observed as an intensity change in B-mode imaging. In addition, the subsequent impulse waves were observed only from the phase change induction in gels. Therefore, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…For those investigating droplet vaporization that produces stable bubbles, the models have generally predicted a monotonic expansion that can be modulated by the influence of the vaporization pulse and inward gas diffusion, which matches experimental data for DDFP microdroplets well (Shpak et al 2013b, 2013a, Wong et al 2011). For these types of droplets, the pressure wavefront generated by the initially high expansion velocities may be able to be detected as a sign of droplet vaporization – similar to the method proposed by Asami et al (Asami et al 2010). Alternative models proposed by Qamar et al (Qamar et al 2010, 2012) have suggested that, depending on droplet size and other physical properties, droplets may over-expand as a result of momentum of expansion and then settle to a final resting diameter in an oscillatory manner, although the experimental results with DDFP microdroplets did not exhibit this behavior.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…For those investigating droplet vaporization that produces stable bubbles, the models have generally predicted a monotonic expansion that can be modulated by the influence of the vaporization pulse and inward gas diffusion, which matches experimental data for DDFP microdroplets well (Shpak et al 2013b, 2013a, Wong et al 2011). For these types of droplets, the pressure wavefront generated by the initially high expansion velocities may be able to be detected as a sign of droplet vaporization – similar to the method proposed by Asami et al (Asami et al 2010). Alternative models proposed by Qamar et al (Qamar et al 2010, 2012) have suggested that, depending on droplet size and other physical properties, droplets may over-expand as a result of momentum of expansion and then settle to a final resting diameter in an oscillatory manner, although the experimental results with DDFP microdroplets did not exhibit this behavior.…”
Section: Introductionmentioning
confidence: 87%
“…Asami et al have suggested that the impulse wavefront from droplets vaporizing adjacent to a rigid boundary could be detected and used to characterize tissue properties (Asami et al 2010). More recently, Reznik et al have suggested that as bubbles produced from vaporized dodecafluoropentane (DDFP, boiling point 29°C) droplets evolve over the course of several hundred milliseconds, the change in scattered fundamental and harmonic power over time could be used to differentiate growing bubbles (produced by recently vaporized droplets) from nearby stable bubbles (Reznik et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggest that ultrasound in the presence of microbubbles, including those created by vaporized nanodroplets, transiently permeabilizes the cell nucleus and allows penetration of therapeutic drugs into the nucleus. Asami and colleagues have also proposed that nanoscale PCCAs could be used to characterize viscoelastic properties of tumors by analyzing the waveforms received post-vaporization [114]. …”
Section: Pcca Applicationsmentioning
confidence: 99%
“…Asami et al . have shown that droplet activation behavior is influenced by the viscoelastic properties of a tissue phantom (when the droplets are embedded directly in the phantom) [52]. The peak intensity of the impulse wave was reduced with increasing tissue stiffness.…”
Section: Discussionmentioning
confidence: 99%